Analysis Of Physical Activity Of Home Scale Based SAQ (Speed, Agility, Quickness) In The Time Of Adaptation To New Habits (AKB) For Increase Immune - Fakhri Fajrin Kurniawan; Yayan Wardiyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Physical activity of home-scale based SAQ (Speed, Agility, Quickness) is knowing body movements such as walking, running, jumping, but always requires energy. Athletes are required to maintain physical fitness and maintain body immunity, during the Covid-19 pandemic during the Adaptation of New Habits (AKB). Physical activity of home-scale based SAQ (Speed, Agility, Quickness) is very good for boosting the body's immune system during Adaptation to New Habits (AKB). This research analyzes physical activity of home scale based SAQ (Speed, Agility, Quickness) in the time of adaptation to new habits (AKB) for increased immunity. This is an observational study with case control design. The sample of this study consisted of 20 case groups and 20 control groups selected from the best athletes in Cirebon Regency. The research instrument was a physical fitness test and a physical activity questionnaire for basketball athletes in Cirebon Regency. The results of this study indicate that physical activity has a significant risk factor for increasing body immunity, this can be seen from the Odds Ratio (OR) value of 8.181 with 95% Confidence Interval (CI) of 3.181-21.035. So about 62.5% of the total respondents studied have high physical abilities. While the results of the home-scale physical statistical test based on SAQ (Speed, Agility, Quickness) then the Odds Ratio (OR) value is 14,578 with 95% Confidence Interval (CI) 5,083-41,809, this shows that basketball athletes who physically scale at home SAQ ( Speed, Agility, Quickness) experienced better physical improvement compared to those who carried out normal physical activities in the Covid-19 pandemic situation. The conclusion of this study is that home-scale physical activity based on SAQ (Speed, Agility, Quickness) during Adaptation of New Habits (AKB) can improve the body's immune system.